IPAS teachers’ perspectives on digital literacy as a pedagogical foundation in the age of AI - Muriani Nur Hayati; Fahmi Fatkhomi; Yovian Prasetya (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to determine the perspective of digital literacy as a pedagogical foundation for IPAS teachers in the era of artificial intelligence. This study uses a qualitative approach with thematic analysis through interviews. Interviews were conducted with five IPAS vocational school teachers in the Tegal Regency. The results revealed that teachers view digital literacy as a crucial skill in utilizing digital tools and interactive digital platforms, with teachers' opinions differing significantly depending on their length of teaching experience. Three main challenges faced include limited infrastructure, student resistance, and the need for ongoing training. The findings show that teachers position AI only as a learning assistant that enriches the learning experience. The implications of the study emphasize the development of applicable digital literacy training programs and recommend collaboration among teachers through learning communities to improve teachers' pedagogical competencies. Keywords: digital literacy; artificial intelligence; pedagogical; IPAS teacher